Are offshore platforms a good candidate to restore functional diversity of reef fish communities in the Arabian Gulf? - Rodrigo, Riera (2023)
Human-made structures are ubiquitous in the marine realm. Complex structures such as oil and gas platforms may constitute a suitable habitat for species in areas where natural reefs have been highly degraded by coastal development. We here explore the suitability of fish assemblages associated to offshore platforms as surrogates for depleted fish stocks from coastal areas. Taxonomic and functional diversity have been used as approaches to test this hypothesis. Beta diversity components (nestedness and turnover) have also been assessed to unveil the magnitude of the differences between fish-associated communities from offshore platforms and natural reefs. The results showed a sharp difference between natural and artificial reef assemblages, suggesting that these artificial structures may not be suitable candidates serving as surrogates of fish assemblages. Natural reefs were characterized by a depletion of species and abundances, typical of overfished sites, together with other factors such as depth and substrate complexity. Reefs at medium depth in the eastern part of oil platforms, i.e. Kharaza, Maydam Mahzam and Fast east-Halul, showed the highest species richness (19–25 taxa) and functional richness. Thus, our results showed that offshore platforms harbor different fish species composition and community structures than natural reefs. Hence, the conservation of natural reefs under pressure, and artificial systems that act as marine protected areas are of utmost importance to preserve the fish biodiversity in the region. From our perspective, an integrative management of both natural and artificial structures is urgently needed, considering the extensive number of installations that will be decommissioned in the study region. The present results have ecological implications of utmost importance that need to be considered in coastal planning of the Arabian Gulf where a substantial portion of natural reefs have been drastically transformed.